An examination of the relative age effect in developmental girls` hockey in Ontario - Smith, K. L.; Weir. P. L. (High Ability Studies, 2013)
The relative age effect (RAE) suggests that athletes may be provided with greater opportunities for success depending on the position of their birthdate in a sport`s selection year. While the effect has been well established in men`s sports, less is known about women`s sports. This study examined the RAE in developmental girls` hockey in Ontario. Relative age, player position, age division, and level of play were provided by the Ontario Women`s Hockey Association for 36,555 registrants. Older players were over-represented, and younger players under-represented across all age divisions and levels of play. This suggests that the RAE is present in developmental girls` hockey, the magnitude of which varies with level of play and player position.